Characterization of soluble thrombomodulin levels in patients with stage 3–5 chronic kidney disease. (June 2014) - Bao, Yu-Shi; Jia, Xi-Bei; Wang, Dong; Liu, Rui-Chan; Zou, Chun-Bo; Na, Shi-Ping
Abstract Objective: This study aims to test the serum levels of soluble thrombomodulin (TM) in patients with chronic kidney disease (CKD)3–5 and to assess their connection with the different stages and severity of disease. Methods: Sixty-seven patients with CKD are included, disease severity was evaluated accordingly to CKD staging and clinical data is collected. Nineteen healthy volunteers served as healthy controls. Serum soluble TM is analyzed by ELISA. Results: The levels of soluble TM in all patients with CKD were significantly higher than those of healthy controls (p < 0.001). CKD5 patients showed higher serum levels of soluble TM, in comparison to CKD4 patients (p = 0.001), CKD3 patients (p < 0.001), and healthy controls (p < 0.001). The correlation analysis revealed significant correlation between serum soluble TM and disease severity (r = 0.714, p < 0.001). Serum soluble TM was found to be correlated with eGFR (r = −0.766; p < 0.001) and serum creatinine (r = 0.778, p < 0.001). Conclusion: Soluble TM concentrations significantly increase in the CKD patients and are associated with the severity of the disease. Soluble TM may play critical roles in the development of CKD, as a biomarker of endothelial cells damage, anticoagulation and anti-inflammation.